Analisis Persepsi Wanita Usia Subur Terhadap Inspeksi Visual Asam Asetat (IVA) Dalam Deteksi Dini Kanker Serviks Di Puskesmas Kassi-Kassi Kota Makassar - Bulqis; Yusriani; Arman (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
Cervical cancer is cancer that attacks the cervical area orcervix, which is the lower area of ​​the uterus that connects theuterus and vagina. This cancer can be detected early using theIVA (Visual Inspection of Acetic Acid) method. The high level ofcervical cancer cannot be separated from knowledge thatincludes the risks, symptoms and prevention in the community, especially women of childbearing age, which are still very lowso it is necessary to apply the Health Belief Model (HBM) theory for making a decision on a disease to protect themselvesby their perceptions. The purpose of this study was to analyzethe effect of perceptions of women of childbearing age based onthe theory of health belief models (knowledge, perceived threats, benefits) on VIA examination. This type of research is a quantitative research method using a cross-sectional approach. Sampling using non-probability sampling technique withpurposive sampling method with a sample of 208 women ofchildbearing age. Data analysis was carried out univariately, bivariately using chi square test and multivariate using multiplelogistic regression test. The results showed that there was a relationship between knowledge and VIA examination with a value of 0.000 <0.05. There is a relationship between perceivedthreat and IVA examination with a value of 0.017 < 0.05, andthere is a relationship between perceived benefits and an IVA examination with a value of 0.003 < 0.05. This study suggeststhat the public, especially women of childbearing age andmarried, are advised to play an active role in seeking the widestpossible information about reproductive health, especiallycervical cancer and examination with the IVA test as well as increasing awareness to carry out the examination.